The evolution and future of influenza pandemic preparedness - Harrington, Walter N.; Kackos, Christina M.; Webby, Richard J. (Experimental & molecular medicine, 2021)
The influenza virus is a global threat to human health causing unpredictable yet recurring pandemics, the last four emerging over the course of a hundred years. As our knowledge of influenza virus evolution, distribution, and transmission has increased, paths to pandemic preparedness have become apparent. In the 1950s, the World Health Organization (WHO) established a global influenza surveillance network that is now composed of institutions in 122 member states. This and other surveillance networks monitor circulating influenza strains in humans and animal reservoirs and are primed to detect influenza strains with pandemic potential. Both the United States Centers for Disease Control and Prevention and the WHO have also developed pandemic risk assessment tools that evaluate specific aspects of emerging influenza strains to develop a systematic process of determining research and funding priorities according to the risk of emergence and potential impact. Here, we review the history of influenza pandemic preparedness and the current state of preparedness, and we propose additional measures for improvement. We also comment on the intersection between the influenza pandemic preparedness network and the current SARS-CoV-2 crisis. We must continually evaluate and revise our risk assessment and pandemic preparedness plans and incorporate new information gathered from research and global crises. Influenza: Learning to plan for pandemics The long history of combating and planning for influenza pandemics should inform the fight against novel coronaviruses such as SARS-Cov-2. Richard Webby and co-workers at St. Jude Children’s Research Hospital in Memphis, USA review the history of preparing for influenza pandemics, including the global influenza surveillance network set up by the World Health Organization (WHO) in the 1950s. The 2009 H1N1 pandemic prompted WHO and the US Centers for Disease Control and Prevention to develop more detailed risk assessment tools drawing on laboratory research, genomics, industrial vaccine development, and surveillance of emerging animal strains that might transfer to humans. These tools and experience are proving successful in containing the H7N9 influenza that emerged in 2013, and could serve as models for managing coronaviruses, whose pandemic potential has only become apparent in the past two decades.